Redundancy and evolution of GATA factor requirements in development of the myocardium. - Peterkin, T; Gibson, A; Patient, R (2007)
The transcription factors, GATA4, 5 and 6, recognize the same DNA sequence and are all expressed in the developing myocardium. However, knockout studies in the mouse have indicated that none of them are absolutely required for the specification of the myocardium. Here we present evidence for redundancy in this family for the first time. Using morpholinos in both Xenopus and zebrafish embryos, we show that GATA4 knockdown, for example, only affects cardiac marker expression in the absence of either GATA5 or GATA6. A similar situation pertains for GATA5 in Xenopus whereas, in zebrafish, GATA5 (faust) plays a major role in driving the myocardial programme. This requirement for GATA5 in zebrafish is for induction of the myocardium, in contrast to the GATA6 requirement in both species, which is for differentiation. This early role for GATA5 in zebrafish correlates with its earlier expression and with an earlier requirement for BMP signalling, suggesting that a mutual maintenance loop for GATA, BMP and Nkx expression is the evolutionarily conserved entity.